Porous nano composite Co / TiO2atCN catalyst and preparation and application thereof

Prepare porous nano-composite CO/TIO2@cn catalysts through MOFS extension growth method and high temperature thermal solution technology to form a heterogeneous structure of CO and TiO2, solving the existing TIO2 photocatalytic material in the light and light-lit electron-floor-to-open acupoint pairs The problem of composite has achieved efficient visible under -light dye degradation.

CN119368213AActive Publication Date: 2025-01-28GUANGDONG UNIV OF EDUCATION

Patent Information

Application Number
CN202411398504.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-28
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The photoresponse range of existing TiO2 photocatalytic materials is mainly concentrated in the ultraviolet light area, and the photogenerated electron-hole pairs are easy to recombinate, resulting in low photocatalytic efficiency and difficult to efficiently degrade dyes under visible light.

Method used

ZIF-67@NH2-MIL-125 composite structure is synthesized through the MOFS extension growth method, and more porous nano-composite CO/TIO2@CN catalysts are used to form a heterogeneous structure of CO and TIO2 through high temperature thermal decomposition to improve the optical activity of optical catalytic.

Benefits of technology

The high -efficiency photocatalytic degradation infection of the catalyst was achieved. The degradation rate of Roddamum Ming B reached 98.2%, which significantly improved the photocatalytic efficiency, and the preparation process was simple, the cost was low, and it was suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and discloses a porous nano composite Co / TiO2atCN catalyst and preparation and application thereof. According to the preparation method, a ZIF-67 (at) NH2-MIL-125 composite structure is synthesized by utilizing an MOFs epitaxial growth method strategy, and a metal / titanium dioxide / carbon nitrogen compound (Co / TiO2 (at) CN) is further prepared by taking the ZIF-67 (at) NH2-MIL-125 composite structure as a sacrificial template through high-temperature pyrolysis. The method disclosed by the invention has the advantages of simple preparation process and low cost. The obtained composite material has excellent photocatalytic activity, and the problem that a single semiconductor material is low in photocatalytic efficiency can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a porous nano-composite Co / TiO2@CN catalyst and a preparation and application thereof. Background Art

[0003] Photocatalytic technology has shown great application potential in the field of dye wastewater treatment because it can completely degrade organic pollutants into harmless small molecules (such as CO2 and H2O) under light conditions. Semiconductor photocatalytic materials are the core of photocatalytic degradation of dyes. This type of material has a unique electronic structure. When exposed to light, it can generate photogenerated electrons and holes. These active carriers can participate in redox reactions to generate highly oxidizing active substances (such as OH radicals, O2⁻superoxides, etc.), thereby decomposing complex organic dyes into harmless small molecules. Therefore, semiconductor materials have become an ideal choice for photocatalytic degradation of dyes due to their excellent photogenerated electron-hole generation ability, chemical stability and environmental friendliness.

[0004] Titanium dioxide (TiO2), as a typical photocatalytic material, has been widely used in the field of environmental purification due to its excellent photocatalytic activity, chemical stability, non-toxicity and low cost. However, the photoresponse range of TiO2 is mainly concentrated in the ultraviolet region (wavelength <387nm), which only accounts for about 5% of the solar spectrum, greatly limiting its application under visible light. In addition, the photogenerated electron-hole pairs of TiO2 are easy to recombine, further reducing its photocatalytic efficiency. To overcome these shortcomings, researchers have tried a variety of methods, such as metal ion doping, non-metallic doping, heterojunction construction and precious metal deposition, to expand the photoresponse range of TiO2 and improve its photocatalytic activity. Although these improvements have made some progress, TiO2-based composites still face challenges in terms of photoresponse range, inhibition of photogenerated electron-hole recombination and material stability.

[0005] Therefore, how to improve the photocatalytic performance of materials by optimizing the preparation method and how to achieve efficient degradation of dyes in actual environments are issues that need to be urgently addressed in current research. Summary of the invention

[0006] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a porous nanocomposite Co / TiO2@CN catalyst.

[0007] The present invention innovatively uses the MOFs epitaxial growth strategy to synthesize the ZIF-67@NH2-MIL-125 composite structure, and uses it as a sacrificial template to further prepare a metal / titanium dioxide / carbon nitrogen composite (Co / TiO2@CN) through high-temperature pyrolysis. This technology has the advantages of simple preparation process and low cost. The composite material prepared by this method has excellent photocatalytic activity and can effectively solve the problem of low photocatalytic efficiency of single semiconductor materials.

[0008] Another object of the present invention is to provide a porous nanocomposite Co / TiO2@CN catalyst prepared by the above method.

[0009] Another object of the present invention is to provide application of the above-mentioned porous nanocomposite Co / TiO2@CN catalyst in photocatalytic degradation of dyes.

[0010] The purpose of the present invention is achieved through the following solutions: A method for preparing a nanocomposite Co / TiO2@CN catalyst comprises the following steps: (1) 2-aminoterephthalic acid, titanium source, methanol and solvent are mixed uniformly, heated for reaction, washed and dried to obtain NH2-MIL-125 powder; (2) uniformly mixing NH2-MIL-125 powder, 2-methylimidazole, cobalt salt and solvent, stirring for reaction, washing and drying to obtain ZIF-67@NH2-MIL-125 powder; (3) Under an inert atmosphere, the ZIF-67@NH2-MIL-125 powder was pyrolyzed and cooled to obtain a nanocomposite Co / TiO2@CN catalyst.

[0011] The titanium source in step (1) is at least one of isopropyl titanate and tetra-n-butoxytitanium (Ti(OBu)4).

[0012] The solvent in step (1) is at least one of N,N-dimethylformamide (DMF) and dimethylacetamide (DMAc).

[0013] In step (1), the molar ratio of the 2-aminoterephthalic acid to the titanium in the titanium source is 1-4:1.

[0014] The molar ratio of 2-aminoterephthalic acid to methanol in step (1) is 1:100-200.

[0015] The volume ratio of the solvent to methanol in step (1) is 1-5:1.

[0016] The temperature of the heating reaction in step (1) is 120°C-180°C, preferably 150°C.

[0017] The heating reaction time in step (1) is 10-72 hours, preferably 15-24 hours.

[0018] The washing in step (1) is centrifugal washing, wherein the reagent for the centrifugal washing is at least one of methanol, ethanol and acetone.

[0019] The drying in step (1) and step (2) is either vacuum drying or oven drying; the drying temperature is 60°C-120°C, and the drying time is 6-24h.

[0020] The cobalt salt in step (2) is at least one of Co(NO3)2·6H2O, (CH3COO)2Co·6H2O, and CoCl2·6H2O.

[0021] The solvent in step (2) is at least one of methanol and water.

[0022] The amount of the solvent used in step (2) is such that the concentration of the cobalt salt in the mixed solution is 5-100 mM.

[0023] In step (2), the mass ratio of the NH2-MIL-125 powder to 2-methylimidazole is 1:5-10.

[0024] The molar ratio of cobalt to 2-methylimidazole in the cobalt salt of step (2) is 1:1-8.

[0025] The stirring reaction in step (2) is carried out at room temperature for 1-10 hours, preferably 2-4 hours.

[0026] The inert atmosphere in step (3) is argon or nitrogen, preferably nitrogen.

[0027] The heating rate of the pyrolysis in step (3) is 1-20°C / min, more preferably 10°C / min.

[0028] The pyrolysis temperature in step (3) is 600-900°C, preferably 700-800°C.

[0029] The holding time of the pyrolysis in step (3) is 1-10 h, preferably 2 h.

[0030] The cooling in step (3) is cooling to room temperature.

[0031] Nanocomposite Co / TiO2@CN catalyst prepared by the above method.

[0032] Application of the above-mentioned nanocomposite Co / TiO2@CN catalyst in photocatalytic degradation of dyes.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention provides a simple and efficient method for preparing a porous nanocomposite Co / TiO2@CN catalyst. The method can synthesize a catalyst with excellent performance only through basic operations such as solution mixing, stirring and pyrolysis. The entire preparation process does not require complex equipment or the use of expensive precious metal materials, so it is suitable for large-scale production and has significant economic advantages. In addition, the preparation process follows the principle of green environmental protection and meets the requirements of modern industry for sustainable development.

[0034] (2) The present invention utilizes MOF materials as precursors, so that the resulting catalyst has a porous structure, which provides abundant pores and channels, thereby improving the mass transfer capacity and obtaining excellent catalytic performance.

[0035] (3) In the catalyst preparation process of the present invention, Co and TiO2 form an effective heterojunction structure through pyrolysis. This heterojunction can effectively promote the transfer of photogenerated electrons from TiO2 to Co, thereby reducing the recombination probability of electron-hole pairs, extending the life of photogenerated carriers, and further improving the photocatalytic efficiency. At the same time, the presence of the heterojunction also improves the electron transmission path, reduces the loss in the charge transmission process, and makes the photocatalytic reaction more efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the scanning electron microscope (SEM) image of ZIF-67@NH2-MIL-125 of Example 1.

[0037] Figure 2 This is the scanning electron microscope (SEM) image of Co / TiO2@CN-700 of Example 1.

[0038] Figure 3 X-ray diffraction (XRD) patterns of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0039] Figure 4 This is a graph showing the photocatalytic reaction performance test results of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0041] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0042] Example 1 (1) Preparation of NH2-MIL-125 217 mg of 2-aminoterephthalic acid, 0.14 mL (0.47 mmol) of isopropyl titanate, 5 mL of N,N-dimethylformamide (DMF) and 5 mL (0.124 mol) of methanol were mixed and added to a reactor, and evenly dispersed by ultrasonic treatment. The reactor was sealed and placed in an oven, heated to 150 ° C, and kept at this temperature for 15 hours. After the reaction was completed, the product was washed with methanol several times to remove the unreacted products, and then dried in an oven at 100 ° C for 10 hours to obtain NH2-MIL-125 nanocrystals. The crystals were regular disc-shaped with a diameter of about 700-1000 nm.

[0043] (2) Preparation of ZIF-67@NH2-MIL-125 4 mg of NH2-MIL-125 was placed in a round-bottom flask, 1 mL of methanol was added and it was evenly dispersed by ultrasonic treatment. 30 mg of 2-methylimidazole and 52 mg of Co(NO3)2·6H2O were dissolved in 3 ml and 5 ml of methanol respectively and ultrasonically dispersed until uniform. Under continuous stirring, the above two methanol solutions were slowly added dropwise to the NH2-MIL-125 suspension and reacted at room temperature for 4 hours. After the reaction, the product was washed with methanol several times to remove unreacted products and impurities, and then dried in an oven at 100 ° C for 10 hours to obtain ZIF-67@NH2-MIL-125 powder.

[0044] (3) Preparation of Co / TiO2@CN-700 materials 50 mg of ZIF-67@NH2-MIL-125 powder was placed in a tube furnace and heated to 700°C at a rate of 10°C / min under nitrogen protection, and the temperature was maintained for 2 hours of pyrolysis reaction. After the reaction was completed, the furnace temperature was naturally cooled to room temperature and the Co / TiO2@CN-700 catalyst was collected.

[0045] The Co / TiO2@CN-700 catalyst was used in the photocatalytic degradation of dye (Rhodamine B). The specific reaction steps are as follows: Weigh 15 mg of Co / TiO2@CN-700 catalyst and add it to a beaker containing 50 mL of Rhodamine B solution (initial concentration 2.5 mg / L). Stir in a dark environment for 30 minutes to allow the catalyst and solution to reach adsorption equilibrium. Place the beaker under a xenon light source for 1 hour of photocatalytic reaction. After the reaction, take a sample and use a UV-visible spectrophotometer to measure the absorbance of Rhodamine B at a wavelength of 554 nm. Calculate the degradation rate of the dye based on the change in absorbance.

[0046] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is: the degradation rate of Rhodamine B reaches 98.2%.

[0047] Example 2 The difference from Example 1 is that the amount of isopropyl titanate added in step (1) is 0.18 ml (0.60 mmol), and NH2-MIL-125 crystals with larger particle size are prepared, with a diameter of about 1.5-2.5 μm.

[0048] The performance index of the obtained catalyst in the photocatalytic degradation reaction of Rhodamine B is: the degradation rate of Rhodamine B reaches 93.1%.

[0049] Example 3 The difference from Example 1 is that the amount of isopropyl titanate added in step (1) is 0.10 ml (0.34 mmol), and NH2-MIL-125 crystals with smaller particle size are prepared, and the diameter of the crystals is about 300-500 nm.

[0050] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is: the degradation rate of Rhodamine B reaches 88.7%.

[0051] Example 4 The difference from Example 1 is that in step (2), after adding 2-methylimidazole and Co(NO3)2·6H2O methanol solution, the reaction was carried out at room temperature for 2 hours, and the surface of the obtained ZIF-67@NH2-MIL-125 showed an uneven structure, and ZIF-67 was less distributed on the surface of NH2-MIL-125.

[0052] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is: the degradation rate of Rhodamine B reaches 70.3%.

[0053] Example 5 The difference from Example 1 is that in step (3), 50 mg of ZIF-67@NH2-MIL-125 powder is placed in a tube furnace, heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere, and maintained at this temperature for pyrolysis for 2 hours to obtain a Co / TiO2@CN-800 catalyst. The particle size of the Co nanoparticles on the surface of the Co / TiO2@CN-800 material prepared at this pyrolysis temperature is significantly increased.

[0054] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is: the degradation rate of Rhodamine B is 97.8%.

[0055] Example 6 Weigh 15 mg of the Co / TiO2@CN-700 catalyst prepared in Example 1 and add it to a beaker containing 50 mL of Rhodamine B solution (initial concentration 5 mg / L). Stir for 30 minutes in a dark environment to allow the catalyst and the solution to reach adsorption equilibrium. Place the beaker under a xenon light source for 1 hour of photocatalytic reaction. After the reaction is completed, take a sample and use a UV-visible spectrophotometer to measure the absorbance of Rhodamine B at a wavelength of 554 nm. Calculate the degradation rate of the dye based on the change in absorbance.

[0056] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is: the degradation rate of Rhodamine B reaches 60.3%.

[0057] Comparative Example 1 The difference from Example 1 is that the Co@CN catalyst is prepared by pyrolyzing ZIF-67, and the specific steps are as follows: (1) Preparation of ZIF-67 30 mg of 2-methylimidazole and 52 mg of cobalt nitrate hexahydrate were added to 3 mL and 5 mL of methanol for dispersing and dissolving, respectively. Under stirring conditions, the 2-methylimidazole methanol solution was added to the cobalt nitrate hexahydrate methanol solution, mixed evenly, and then allowed to react for 24 hours. After the reaction was completed, ZIF-67 crystals were obtained by centrifugation.

[0058] (2) Preparation of Co@CN catalyst 50 mg of ZIF-67 powder was placed in a tube furnace, heated to 700°C at 10°C / min under nitrogen protection, and maintained at this temperature for pyrolysis for 2 h. When the furnace temperature naturally dropped to room temperature, the Co@CN catalyst was collected.

[0059] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is as follows: the degradation rate of Rhodamine B is 11.3%.

[0060] Comparative Example 2 The difference from Example 1 is that the TiO2@CN catalyst is prepared directly by pyrolyzing NH2-MIL-125. The specific steps are as follows: (1) Preparation of NH2-MIL-125 217 mg of 2-aminoterephthalic acid, 0.14 mL of isopropyl titanate, 5 mL of N,N-dimethylformamide (DMF) and 5 mL of methanol were mixed and added to the reactor, and evenly dispersed by ultrasonic treatment. The reactor was sealed and placed in an oven, heated to 150 ° C, and maintained at this temperature for 15 hours. After the reaction was completed, the product was washed with methanol several times to remove the unreacted products, and then dried in an oven at 100 ° C for 10 hours to obtain NH2-MIL-125 powder.

[0061] (2) Preparation of Co / TiO2@CN catalyst 50 mg of NH2-MIL-125 powder was placed in a tube furnace, heated to 700°C at a rate of 10°C / min under nitrogen protection, and maintained at this temperature for pyrolysis for 2 h. When the furnace temperature naturally dropped to room temperature, the TiO2@CN catalyst was collected.

[0062] The performance index of the obtained catalyst in the photocatalytic degradation of Rhodamine B is: the degradation rate of Rhodamine B is 93.2%.

[0063] Analysis of attached pictures: Figure 1 This is a scanning electron microscope (SEM) image of ZIF-67@NH2-MIL-125, which shows that the material is disc-shaped as a whole and the surface is evenly covered with ZIF-67 particles.

[0064] Figure 2 This is the SEM image of Co / TiO2@CN-700 obtained in Example 1. The image shows that the material still has a disc-shaped structure after pyrolysis, and the surface is evenly covered with Co particles.

[0065] Figure 3 The X-ray diffraction (XRD) spectrum shows that Co@CN has diffraction peaks at 44.2°, 51.5°, and 75.8°, corresponding to the (111), (200), and (220) crystal planes of face-centered cubic Co. TiO2@CN has diffraction peaks at 27.4°, 36.1°, 41.2°, and 54.3°, corresponding to the (110), (101), (111), and (211) crystal planes of rutile phase TiO2. Co / TiO2@CN-700 has diffraction peaks at the above positions. This indicates that a composite structure in which Co and TiO2 crystal phases coexist has been formed, and Co and TiO2 particles are evenly distributed in the carbon nitrogen (CN) carrier.

[0066] Figure 4 The photocatalytic reaction performance test results of the catalyst are shown in the figure. As shown in the figure, the activity of Co@CN and TiO2@CN catalysts is relatively low. After one hour of reaction, the degradation rates of Rhodamine B are 11.3% and 93.2%, respectively. However, the activity of the Co / TiO2@CN-700 catalyst, which is a composite of Co and TiO2, is enhanced. After one hour of reaction, the degradation rate of Rhodamine B reaches 98.9%. This shows that the Co / TiO2@CN catalyst of the present invention exhibits better performance in the photocatalytic degradation of dyes.

[0067] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocomposite Co / TiO2@CN catalyst, characterized in that: The following steps are involved: (1) 2-aminoterephthalic acid, titanium source, methanol and solvent are mixed uniformly, heated for reaction, washed and dried to obtain NH2-MIL-125 powder; (2) uniformly mixing NH2-MIL-125 powder, 2-methylimidazole, cobalt salt and solvent, stirring for reaction, washing and drying to obtain ZIF-67@NH2-MIL-125 powder; (3) Under an inert atmosphere, the ZIF-67@NH2-MIL-125 powder was pyrolyzed and cooled to obtain a nanocomposite Co / TiO2@CN catalyst.

2. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The titanium source in step (1) is at least one of isopropyl titanate and tetra-n-butoxytitanium; The solvent in step (1) is at least one of N,N-dimethylformamide and dimethylacetamide.

3. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The molar ratio of the 2-aminoterephthalic acid to the titanium in the titanium source in step (1) is 1-4:1; The molar ratio of 2-aminoterephthalic acid to methanol in step (1) is 1:100-200; The volume ratio of the solvent to methanol in step (1) is 1-5:

1.

4. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The temperature of the heating reaction in step (1) is 120°C-180°C; The heating reaction time in step (1) is 10-72 hours; The drying in step (1) and step (2) is either vacuum drying or oven drying; the drying temperature is 60°C-120°C, and the drying time is 6-24h.

5. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The cobalt salt in step (2) is at least one of Co(NO3)2·6H2O, (CH3COO)2Co·6H2O, and CoCl2·6H2O; The solvent in step (2) is at least one of methanol and water.

6. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The amount of the solvent in step (2) is such that the concentration of the cobalt salt in the mixed solution is 5-100 mM; The mass ratio of the NH2-MIL-125 powder to 2-methylimidazole in step (2) is 1:5-10; The molar ratio of cobalt to 2-methylimidazole in the cobalt salt of step (2) is 1:1-8.

7. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The stirring reaction in step (2) is carried out at room temperature for 1-10 hours.

8. The method for preparing the nanocomposite Co / TiO2@CN catalyst according to claim 1, characterized in that: The inert atmosphere in step (3) is argon or nitrogen; The heating rate of the pyrolysis in step (3) is 1-20°C / min; The pyrolysis temperature in step (3) is 600-900°C, preferably 700-800°C; The holding time of the pyrolysis in step (3) is 1-10h.

9. A nanocomposite Co / TiO2@CN catalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the nanocomposite Co / TiO2@CN catalyst according to claim 9 in photocatalytic degradation of dyes.

Citation Information

Patent Citations

  • Preparation method of composite photocatalyst TiO2 / g-C3N4 derived from MOF (Metal Organic Frameworks)

    CN109046425A

  • MOF-based derived composite photocatalyst and preparation method thereof

    CN111111668A

  • ZIF-67(Co) / hollow microspherical beta-Bi2O3 / g-C3N4 visible-light-driven photocatalyst

    CN113663732A

  • Preparation method of ternary MOF (Metal Organic Framework) derived zinc-titanium nano composite material capable of photocatalytically degrading tetracycline

    CN115106127A

  • Preparation method and application of core-shell Co-CN coated SiO2 catalyst

    CN118341467A

Cited By

  • A supported nano-palladium-silver bimetallic catalyst, a preparation method and application thereof

    CN122722239A